The Use of Podcast to Improve Students' Listening And Speaking Skills For EFL Learners - Alllanbergenova Maxida; Aytmuratova Ayzada (Zien Journals, 2024)
The article is discussed the effectiveness of the postcast in teaching EFL learners through the listening and speaking. The purpose of this study is to investigate how technology tools helped ELLs become more proficient in English. The theory of second language acquisition will be used to make a better understanding in how comprehensive the input theory being delivered using new technology provides learners with comprehensible materials leading to acquire the language faster. He also explains using technology tools as a way of enhancing ELLs language acquisition by providing a rich and comprehensive input that will be relevant in motivating ELLs.
Keywords: Edu technology; Podcast; Listening and Speaking Skills